2005
DOI: 10.1007/s00520-005-0819-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, sociodemographic, and local system factors associated with a hospital death among cancer patients

Abstract: The study identified groups of cancer patients at risk of hospital death. These results should account when planning the allocation of hospital palliative care services as well as when informing policy decisions about health care financing and delivery of these services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
7
1
Order By: Relevance
“…Other researchers have found lower income to be a determinant of in-hospital death [11,15]. If we consider income and education as proxies, our results support the opposite conclusion: cases with higher education, and thus, with higher incomes, were more likely to die in hospitals.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Other researchers have found lower income to be a determinant of in-hospital death [11,15]. If we consider income and education as proxies, our results support the opposite conclusion: cases with higher education, and thus, with higher incomes, were more likely to die in hospitals.…”
Section: Discussioncontrasting
confidence: 65%
“…Clinical factors such as type of cancer [7,10,11], stage at diagnosis [2], comorbidities [8,17], and survival time [15] have been associated with the place of death. Sociodemographic factors such as age [1,12], gender [12,13,15], marital status [1,12,15], race [10,15,16], socio-economic status [11,15], and insurance type [9,24] have also been described as having an impact on the place of death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, patients diagnosed with hematological cancers have increased risk of inhospital death due to infection and/or bleeding, whereas patients diagnosed with breast and gynecological cancers are more likely to die elsewhere. 24 In addition, patients with colorectal cancer are more likely to die in a hospital or inpatient hospice setting than at home. 25 Notably, place of death may vary widely between regions due to differences in the availability of end-of-life care facilities.…”
Section: Place Of Death and End-of-life Carementioning
confidence: 99%
“…Low socioeconomic groups' reliance on acute care services during illness progression and the likelihood of death in acute care facilities were identified by many authors in the review [24][25][26][27][28]. A recent US study identified that palliative care service registration reduced the likelihood of emergency department presentations in a cohort of low income men [29].…”
Section: Availabilitymentioning
confidence: 99%